Respuesta :
Answer:
[tex]y = 7e^{-3t}[/tex]
Step-by-step explanation:
[tex]y = C_1e^{3t} + C_2e^{-3t}[/tex]
[tex]y(0) = 7[/tex] implies that when [tex]t=0[/tex], [tex]y=7[/tex].
[tex]7 = C_1e^{3\times0) + C_2e^{-3\times0}[/tex]
[tex]7 = C_1+C_2[/tex]
For the condition [tex]\lim\limits_{t \to +\infty} y(t) = 0[/tex], as [tex]t\to+\infty[/tex], [tex]y\to0[/tex].
In the expression for [tex]y[/tex], as [tex]t\to+\infty[/tex], the term containing [tex]C_2[/tex] vanishes. Hence,
[tex]0 = C_1e^{3t}[/tex]
[tex]C_1 = 0[/tex]
Since [tex]7 = C_1+C_2[/tex]
[tex]7 = 0+C_2[/tex]
[tex]C_2 = 7[/tex]
Substituting for [tex]C_1[/tex] and [tex]C_2[/tex] in [tex]y[/tex],
[tex]y = 7e^{-3t}[/tex]
The answer is [tex]y = 7e^{-3t}[/tex]
Since [tex]y = c_{1}e^{3t} + c_{2}e^{-3t}[/tex] is a solution to the differential equation y" - 9y = 0, and given that y(0) = 7, [tex]\lim_{t \to +\infty} y(t) = 0[/tex].
The equation
So, [tex]y = c_{1}e^{3t} + c_{2}e^{-3t}[/tex]
[tex]y(0) = c_{1}e^{3(0)} + c_{2}e^{-3(0)}\\7 = c_{1}e^{0} + c_{2}e^{0}\\7 = c_{1} + c_{2}[/tex]
The constants
Also, [tex]\lim_{t \to +\infty} y(t) = 0[/tex]
So, [tex]y(\infty) = c_{1}e^{3(+\infty)} + c_{2}e^{-3(+\infty)}\\0 = c_{1}e^{\infty} + c_{2}e^{-\infty}\\0 = c_{1}\infty + c_{2}(0)\\0 = c_{1}\infty + 0\\0/\infty = c_{1}\\c_{1} = 0[/tex]
Since c₁ = 0, substituting it into c₁ + c₂ = 7, we have
c₁ + c₂ = 7
0 + c₂ = 7
c₂ = 7
The value of y
So, substituting c₁ = 0 and c₂ = 7 into y, we have
[tex]y = c_{1}e^{3t} + c_{2}e^{-3t}\\y = (0)e^{3t} + 7e^{-3t}\\y = 0 + 7e^{-3t}\\y = 7e^{-3t}[/tex]
So, the answer is [tex]y = 7e^{-3t}[/tex]
Learn more about differential equations here:
https://brainly.com/question/18760518